COMMERCIAL AND PROMISING VARIETIES OF SOFT WINTER WHEAT IN THE SYSTEM OF GRAIN QUALITY ASSESSMENT - M. M. Kopus; N. S. Kravchenko; N. G. Ignatieva; D. P. Dorokhova; N. I. Sarycheva (Зерновое хозяйство России, 2018)
The article deals with the results of the assessment of breeding material of soft winter wheat with the use of such express methods of evaluation as SDS-sedimentation and analysis of gliadin electrophoregrams. The purpose of our research is to estimate genetic potential according to grain quality and soft winter wheat tolerance to frost (contribution of prolamins), and to assess real quality of grain (realized in the definite field conditions) using the indexes of SDS-sedimentation. Electrophoresis of prolamin proteins of grain (gliadins) has been carried out with the standard method on a starch gel. SDS-sedimentation has been done according to science-practical recommendations, developed in FSBSI ARRIGC after I.G. Kalinenko. The phased approach allows forming a necessary amount of the samples with good, high and excellent grain quality for the farms of competitive variety testing. It can be proved and characterized by the conventional but difficult technologic methods, which allow the farmers to choose promising, competitive varieties with high quality and productivity when sending them for the State variety testing. The conducted researches showed that in the competitive variety testing the main quantity of the samples of soft winter wheat of intensive type possessed high quality of grain in SDS-sedimentation and complied with the valuable and strong wheat. The promising varieties ‘Kipchak’, ‘Bonus’, ‘Kazachka’, ‘Luchezar’, ‘Aksiniya’ and ‘Nakhodka’ possess the high grain quality. The basic amount of the samples of soft winter wheat of half-intensive type has good, high and excellent grain quality. The promising varieties ‘Admiral’, ‘Krasa Dona’, ‘Kapitan’, ‘Kaprizulya’ and ‘Lilit’ showed the quality of the grain of valuable and strong wheat during the period. For the last years 12 varieties of soft winter wheat developed in ARRIGC after I.G. Kalinenko (‘Admiral’, ‘Krasa Dona’, ‘Kapitan’, ‘Kaprizulya’, ‘Lilit’, ‘Kipchak’, ‘Bonus’, ‘Kazachka’, ‘Luchezar’, ‘Aksiniya’, ‘Lidiya’ and ‘Nakhodka’) were sent to SVT. All commercial and promising varieties of soft winter wheat have a high estimation of allele contents of gliadins. These varieties have no gliadins which negatively effect on grain quality; many of them have Gld1D7-allelle, which positively effect on frost tolerance.